1998
DOI: 10.1016/s0928-8244(98)00083-2
|View full text |Cite
|
Sign up to set email alerts
|

Conditional adherence of Enterococcus faecalis to extracellular matrix proteins

Abstract: The adherence of 44 clinical isolates of Enterococcus faecalis, a common cause of endocarditis, and 13 Enterococcus faecium to substrates of six extracellular matrix (ECM) proteins was examined using 35S-labeled bacteria. One E. faecalis strain, isolated from a patient with endocarditis, adhered to collagen types I and IV and another E. faecalis strain adhered to laminin and to collagen types I and IV. However, most isolates showed little adherence ( < 5% of added cells adhered) when grown at 37 degrees C rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 39 publications
(34 reference statements)
8
54
1
Order By: Relevance
“…Among these factors, MSCRAMMs, which are implicated in initiating infections including endocarditis (33), have drawn considerable attention lately because of their widespread nature in traditional and opportunistic pathogens (5,26). The isolation and characterization of MSCRAMMs from E. faecalis has had limited success, because this organism does not readily adhere to ECM proteins under laboratory growth conditions (34,35), unlike its more aggressive relatives staphylococci and streptococci. Therefore, we recently used a bioinformatics approach and identified several proteins that predict MSCRAMM-like structures (6).…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, MSCRAMMs, which are implicated in initiating infections including endocarditis (33), have drawn considerable attention lately because of their widespread nature in traditional and opportunistic pathogens (5,26). The isolation and characterization of MSCRAMMs from E. faecalis has had limited success, because this organism does not readily adhere to ECM proteins under laboratory growth conditions (34,35), unlike its more aggressive relatives staphylococci and streptococci. Therefore, we recently used a bioinformatics approach and identified several proteins that predict MSCRAMM-like structures (6).…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to CI, CIV, and LN was tested by a previously described assay with some modifications (39). Bacteria were streaked from freezer vials onto BHI agar and incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier investigations on adherence of clinical isolates of Enterococcus faecalis, regardless of their source, showed that most isolates displayed conditional binding to CI, CIV, and mouse LN. The adherence phenotype was termed conditional because it was observed after growth at 46°C, but not, for most isolates, after growth at 37°C (39); in these experiments, we defined adherence as being present if Ͼ5% of total labeled cells were bound to the ECM-coated wells. We then identified a putative collagen binding gene, ace, in the E. faecalis strain V583 partial database (24), and based on structural similarities to Cna of Staphylococcus aureus, followed by some biochemical and biophysical characterization, we assigned a CI binding function to Ace (24).…”
mentioning
confidence: 99%
“…E. faecalis along with Staphylococcus aureus, another major nosocomial pathogen, is primarily an extracellular pathogen and presumably adheres to components of the extracellular matrix (ECM). In fact, earlier studies have shown that enterococci can attach to substrates composed of collagens, laminin, vitronectin, fibronectin, fibrinogen, lactoferrin and thrombospondin (Rozdzinski et al, 2001;Styriak et al, 2002Styriak et al, , 1999Xiao et al, 1998;Zareba et al, 1997). In general, the responsible enterococcal adhesins have not been identified or characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ACE but not CNA appears to bind to laminin. The identification of other enterococcal MSCRAMMs has been complicated by an apparently stringent regulation of the expression of the adhesins in E. faecalis, so that bacteria grown under conventional in vitro conditions usually do not adhere efficiently to the different ECM components (Nallapareddy et al, 2000a;Xiao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%